Why does sharecropping survive? Agrarian institutions and contract choice in Kazakhstan and Uzbekistan - Nozilakhon Mukhamedova; Richard Pomfret (Comparative Economic Studies, 2019)
A century ago, Alfred Marshall demonstrated the inefficiency associated with farmers receiving only a portion of their marginal product. Farmers will supply less labor than under arrangements in which they receive their marginal product; output will be sub-optimal. Explanations of sharecropping are based on market imperfections, e.g., high transactions costs or inability to insure against risk, suggesting that sharecropping should disappear with economic development. Nevertheless, sharecropping survives. In Kazakhstan and Uzbekistan, sharecropping has no legal status but farm surveys provide evidence of its existence. Despite farmers' awareness of the Marshallian paradox, institutional uncertainty contributes to the persistent attractiveness of sharecropping.
Keywords: Q13; O12; J43; D23; 330; sharecropping; Central Asia; agriculture